Stem cells - Cherian, Eapen (Jaypee Brothers Medical, 2011)
Beginning with a basic introduction to the field, this book provides a comprehensive review of the properties and potential uses of stem cells, including stem cells in tissue engineering, cancer, gene therapy and in dental tissues. Stem Cells compares two key types of mammalian stem cell - embryonic and adult. Different stem cell systems are discussed, as well as potential obstacles in the use of human stem cells